2020
DOI: 10.1186/s12910-020-00503-4
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring stakeholder perspectives on the use of biological samples for future unspecified research in Malawi

Abstract: Background: There is growing interest in the collection, storage and reuse of biological samples for future research. Storage and future use of biological samples raise ethical concerns and questions about approaches that safeguard the interests of participants. The situation is further complicated in Africa where there is a general lack of governing ethical frameworks that could guide the research community on appropriate approaches for sample storage and use. Furthermore, there is limited empirical data to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
(34 reference statements)
2
14
0
Order By: Relevance
“…In a study that aimed at exploring stakeholder perspectives on the use of biological samples for future unspecified research in Malawi, participants emphasized the importance of privacy and confidentiality and believed that it should be a top priority. They also indicated that there was a need for the formulation of guidelines to govern sharing and access to samples [ 42 ]. We think that there should be clear justifications for any breach of privacy if samples were to be used for purposes other than research, and this should be regulated by law.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that aimed at exploring stakeholder perspectives on the use of biological samples for future unspecified research in Malawi, participants emphasized the importance of privacy and confidentiality and believed that it should be a top priority. They also indicated that there was a need for the formulation of guidelines to govern sharing and access to samples [ 42 ]. We think that there should be clear justifications for any breach of privacy if samples were to be used for purposes other than research, and this should be regulated by law.…”
Section: Discussionmentioning
confidence: 99%
“…This could partially be explained by the fact that the concept of broad consent and alternative approaches to consent for re-use of biological materials and data has increasingly been discussed in LMICs [13][14][15] . As mentioned in our Background section 16,17 , several challenges have been highlighted in obtaining only specific informed consent; e.g., samples obtained from paediatric and autopsy studies regarded as precious resources, considering the circumstances of the consent process and scarcity of such cases.…”
Section: Discussionmentioning
confidence: 99%
“…This could partially be explained by the fact that the concept of broad consent and alternative approaches to consent for re-use of biological materials and data has increasingly been discussed in LMICs [17][18][19] . As mentioned in our Background section 20,21 , several challenges have been highlighted in obtaining only specific informed consent; e.g., samples obtained from pediatric and autopsy studies regarded as precious resources, considering the circumstances of the consent process and scarcity of such cases.…”
Section: Discussionmentioning
confidence: 99%